An insight into anti-angiogenic and anti-metastatic effects of oridonin: current knowledge and future potentials - Abdullah, Nurul Akmaryanti; Md Hashim, Nur Fariesha; Ammar, Aula; Muhamad Zakuan, Noraina (Multidisciplinary Digital Publishing Institute, 2021)
Cancer is one of the leading causes of death worldwide, with a mortality rate of more than 9 million deaths reported in 2018. Conventional anti-cancer therapy can greatly improve survival however treatment resistance is still a major problem especially in metastatic disease. Targeted anti-cancer therapy is increasingly used with conventional therapy to improve patients’ outcomes in advanced and metastatic tumors. However, due to the complexity of cancer biology and metastasis, it is urgent to develop new agents and evaluate the anti-cancer efficacy of available treatments. Many phytochemicals from medicinal plants have been reported to possess anti-cancer properties. One such compound is known as oridonin, a bioactive component of Rabdosia rubescens. Several studies have demonstrated that oridonin inhibits angiogenesis in various types of cancer, including breast, pancreatic, lung, colon and skin cancer. Oridonin’s anti-cancer effects are mediated through the modulation of several signaling pathways which include upregulation of oncogenes and pro-angiogenic growth factors. Furthermore, oridonin also inhibits cell migration, invasion and metastasis via suppressing epithelial-to-mesenchymal transition and blocking downstream signaling targets in the cancer metastasis process. This review summarizes the recent applications of oridonin as an anti-angiogenic and anti-metastatic drug both in vitro and in vivo, and its potential mechanisms of action.